2000
DOI: 10.1002/(sici)1096-8628(20000306)91:1<68::aid-ajmg13>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of four arylsulfatase A missense mutations G86D, Y201C, D255H, and E312D causing metachromatic leukodystrophy

Abstract: Metachromatic leukodystrophy is a lysosomal storage disease caused by the deficiency of arylsulfatase A. Here we describe a hitherto unknown arylsulfatase A allele carrying a E312D missense mutation and characterize the effects of this and three previously described missense mutations, G86D, Y201C, and D255H, on arylsulfatase A. In transfection experiments no enzyme activity can be expressed from arylsulfatase A cDNAs coding for the D255H substituted enzyme, whereas Y201C and E312D mutations were associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Though extensive information has been collected on ARSA common mutations (Polten, et al, 1991) and some studies have been performed on rare alterations (Berna, et al, 2004;Hermann, et al, 2000;Kappler, et al, 1992;Poeppel, et al, 2005), most of these latter still remain uncharacterized. In this context, functional studies on the mutated alleles, aimed at characterizing the residual enzymatic activity associated with a novel mutation, and consequently better correlating patient's genotype with phenotype, acquire a particular relevance.…”
Section: Resultsmentioning
confidence: 99%
“…Though extensive information has been collected on ARSA common mutations (Polten, et al, 1991) and some studies have been performed on rare alterations (Berna, et al, 2004;Hermann, et al, 2000;Kappler, et al, 1992;Poeppel, et al, 2005), most of these latter still remain uncharacterized. In this context, functional studies on the mutated alleles, aimed at characterizing the residual enzymatic activity associated with a novel mutation, and consequently better correlating patient's genotype with phenotype, acquire a particular relevance.…”
Section: Resultsmentioning
confidence: 99%
“…Generally 3 forms, early onset late infantile (1-2 years of age), juvenile (3-16 years of age), and adult form (Ͼ16 years of age) are distinguished. 59 In the most typical late infantile form, the onset of symptoms include a rapid motor and cognitive deterioration, ataxia, spastic paraparesis, leading eventually to a persistent vegetative state, and death.…”
Section: Metachromatic Leukodystrophy (Mld)mentioning
confidence: 99%
“…In contrast to that observed in X-ALD/AMN, a genotype-phenotype correlation has been suggested in the case of ASA mutations. 59 A benign decrease in the ASA activity can be detected in 1% of the general population without MLD. Two mutations have been associated with this ASA pseudodeficiency, and the frequency of the ASA pseudodeficiency alleles is estimated to be 10% in the population.…”
Section: Metachromatic Leukodystrophy (Mld)mentioning
confidence: 99%
“…It is possible that individuals who have later expression or nonexpression of the ASA allele may be affected by a less virulent form of the mutation and therefore produce residual amounts of the enzyme. 6 It is not clearly understood why some children with low levels of lead (≤20 μg/dL) show the signs of neurodeficiencies displayed by children with high levels of lead. However, the interaction between the heterozygous ASA allele and low lead exposure may be one explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the ASA-deficiency MLD cases are found in the Habbanite Jewish community, approximately 12% of cases can be found in the African Americans population, and 2% in the European American population. 5,6 The heterozygous (Aa) form of ASA allelic variation and the possible interaction with environmental lead in children represent a relatively new area of toxicology research, with relatively little data at this writing. Poretz et al4 suggested that the mutant heterozygous form of the allele ASA may produce a compounded or synergistic effect of environmental lead because of the incomplete ASA enzyme activity.…”
Section: Arylsulfatase Pseudodeficiencymentioning
confidence: 99%